Assessment of spatial suitability to test the most suitable areas for agricultural development in the Abbasiya area (Journal of the College of Basic Education, 2026)
Where the study dealt with the spatial analysis of agricultural production in the Abbasiya district by building a model for the quantities of agricultural production based on the data obtained from the state departments and the field survey in order to see the reality of this activity in the Abbasiya district, as well as dealing with information, statistical data and cartographic models and processing them with efficiency and high accuracy of the level For the districts, raising the productive capacity of the agricultural production activity and addressing the problems arising from the difference in the quantities of production. The following is a cartographic model of the agricultural and plant activity according to the development potential in the Abbasiya district